Structural study of Si1-xGex nanocrystals embedded in SiO2 films - Pinto, S. R. C. (2010)
We have investigated the structural properties of Si1−xGex nanocrystals formed in an amorphous SiO2 matrix by magnetron sputtering deposition. The influence of deposition parameters on nanocrystal size, shape, arrangement and internal structure was examined by X-ray diffraction, Raman spectroscopy, grazing incidence small angle X-ray scattering, and high resolution transmission electron microscopy. We found conditions for the formation of spherical Si1−xGex nanocrystals with average sizes between 3 and 13 nm, uniformly distributed in the matrix. In addition we have shown the influence of deposition parameters on average nanocrystal size and Ge content x.